Morphological stasis and phylogenetic relationships in Tadpole shrimps,Triops(Crustacea: Notostraca) - SUNO-UCHI, NOBUMITSU; SASAKI, FUMIYO; CHIBA, SATOSHI; KAWATA, MASAKADO (Biological journal of the Linnean Society, 1997)
The tadpole shrimp (Triops) is a well-known ‘living fossil’ whose fundamental morphology has been unchanged for over 170 million years. Thus, tadpole shrimps are suitable subjects for the study of morphological stasis. We were able to obtain samples of three species ofTriops(T. granarius, T. longicaudatusandT. cancriformis) from four regions in Japan. Taxonomic species were identified by diagnostic morphology. We inferred phylogenetic relationships between individual samples using mitochondrial 16S rRNA. Carapace shapes were compared among populations using shape coordinate methods. The phylogeny inferred from mtDNA shows thatT. granariusis phylogenetically more similar toT. longicaudatusthan toT. cancriformis. mtDNA sequences did not differ among the populations ofT. granarius. However, there were two distinct phylogenetic species withinT. longicaudatus. In spite of the similarity in fundamental morphological characteristics amongTriopsspecies, mtDNA sequences ofTriopsshowed marked differences among the four phylogenetic species. Among the populations ofT. granarius, the carapace shape of the Fukuoka population was significantly different from those of other populations ofT. granarius. The carapace shape of the Kagawa population ofT. longicaudatuswas more similar to those of the Shizuoka and Kagawa populations ofT. granarius.The shape of the carapace ofT. cancriformiswas significantly different from those ofT. granariusandT. longicaudatus.Thus, taxonomic species, phylogenetic species and populations with similar carapace morphology did not correspond with each other. The present results indicate that most of the morphological change did not occur at the time of speciation (lineage separation) and that morphological stases are important evolutionary patterns, but they are not species-level properties.